Analysis of Support Reaction Curves considering Time-Varying Effect of Shotcrete - Ya-Qiong Wang; Ming-Rui Luo (Advances in Civil Engineering)
The core content of the convergence constraint method is to determine the reasonable support time and support stiffness. The stiffness of shotcrete in supporting structure is dynamic. The support stiffness of shotcrete is roughly calculated in engineering, which results in a waste of materials and increases the risk of construction. Therefore, in this study, considering the time-varying characteristics of shotcrete, combined with the elastic-plastic theory and the space effect of excavation surface, the calculation equation describing the support reaction curve is given. An example is given to show that the stiffness of shotcrete considering time-varying effect is lower than that of shotcrete without time-varying effect, and the difference is the most obvious in the age of 0–3 days. However, in the later stage, the stiffness growth rate of shotcrete considering time-varying effect is higher than that of shotcrete without time-varying effect. This study can predict the whole process of the support reaction curve, which can make the application of the convergence constraint method in tunnel support design more accurate, and provide a theoretical basis for the design of supporting structure in the process of tunnel construction.